2022
DOI: 10.3390/cancers14112762
|View full text |Cite
|
Sign up to set email alerts
|

Validation Study for Non-Invasive Prediction of IDH Mutation Status in Patients with Glioma Using In Vivo 1H-Magnetic Resonance Spectroscopy and Machine Learning

Abstract: The isocitrate dehydrogenase (IDH) mutation status is an indispensable prerequisite for diagnosis of glioma (astrocytoma and oligodendroglioma) according to the WHO classification of brain tumors 2021 and is a potential therapeutic target. Usually, immunohistochemistry followed by sequencing of tumor tissue is performed for this purpose. In clinical routine, however, non-invasive determination of IDH mutation status is desirable in cases where tumor biopsy is not possible and for monitoring neuro-oncological t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…In general, the radiomic method is superior to the 2HG MRS analysis manifesting in heterogeneity assessment, availability, generalizability, and predictive modeling for glioma IDH genotyping ( 45 47 ). IDH mutant gliomas often exhibit significant intratumoral heterogeneity, with diverse regions of aggressiveness, therapy resistance, and molecular characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the radiomic method is superior to the 2HG MRS analysis manifesting in heterogeneity assessment, availability, generalizability, and predictive modeling for glioma IDH genotyping ( 45 47 ). IDH mutant gliomas often exhibit significant intratumoral heterogeneity, with diverse regions of aggressiveness, therapy resistance, and molecular characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of advanced MR techniques has improved the diagnostic performance of AI models. Bumes et al have applied magnetic resonance spectroscopy to build a machine learning model and achieved good diagnostic performance (sensitivity: 82.6%, specificity: 72.7%) [41]. Several advanced MRI techniques have also been applied to build AI models, such as DWI, ADC, T1 perfusion and ASL.…”
Section: Genetics and Molecular Marker Detectionmentioning
confidence: 99%
“…To date, no consensually approved method exists to determine IDH status in a noninvasive manner. Nevertheless, some studies using magnetic resonance imaging (MRI) radiomics [8] have shown high accuracy in predicting IDH status, with an area under the curve (AUC) > 0.9, using magnetic resonance (MR) spectroscopy with hydroxyglutarate, among other methods [9]. Conventional MRI represents the gold standard for the initial morphologic evaluation of a suspected brain tumor due to its high spatial resolution.…”
Section: Introductionmentioning
confidence: 99%